IMPLEMENTASI REMOTE DESKTOP UNTUK ERROR LS OBSERVER PADA BALMON SFR KELAS II MATARAM - Ahmad Darusman; Giri Wahyu Wiriasto (Jurnal Bakti Nusa, 2026)
This community service activity aims to increase the capacity of technicians at the Balai Monitor (Balmon) SFR Class II Mataram in handling technical issues on the LS Observer application, specifically connection failures between the Central Monitoring Software (CMS) and the Remote Monitoring Unit (RMU) at the Central Lombok Site. This problem previously halted real-time spectrum monitoring, which is crucial for frequency security. The implemented solution is Remote Desktop Protocol (RDP) for remote troubleshooting. The implementation methods included problem identification, technical training, and RDP implementation. The results show a significant increase in efficiency, with system downtime reduced from an average of 3 hours (via physical visits) to less than 15 minutes through remote access. Partners can now perform independent system recovery without being constrained by geographical distance.